How do Internet moms raise children? The reshaping of Chinese urban women’s parenting psychology by COVID-19 online practices - Zhao, Ru; Ju, Gaofei (Frontiers in Psychology, 2022)
With the acceleration of social transformation and “mediatization,” urban women’s parenting practices have become an important factor affecting the demographic structure and national development. The global COVID-19 pandemic has further contributed to the networking of social life and the creation of “Internet moms” who rely on the Internet for parenting interactions. Using a mixed-methods design, this paper conducted participant observation and in-depth interviews with 90 mothers from various industries born after 1980/1990 across multiple geographies in China to examine the impact of urban women’s Internet practices on the psychology and practice of parenting during the COVID-19 pandemic, as well as how they were empowered by media technologies to practice motherhood and complete their role socialization through the sharing of parenting information, experiences, and actions. The purpose of this qualitative study was to investigate the changing impact of Internet-based parenting practices on Chinese urban women’s daily lives during the COVID-19 pandemic. Through the analysis of these influences, it was found that the whole society, including urban parenting groups, paid attention to self-expression and self-worth and further hoped to arouse society’s recognition, face up to the identity of “mother” and “female,” and give more attention and support to women. The study also found that, as interpersonal communication channels were hindered during the COVID-19 pandemic, the power of the Internet, represented by social media, has created a new platform for information empowerment, action mutual, and ideation of motherhood for urban women formerly bound to family and parenting matters. From individual, family, and individual parenting experiences to group, social, and shared scenarios, urban women are engaged in emotional and memory interactions, including motherhood-related expression, experiences, and collaboration. This shift from virtual to physical has reshaped their parenting view, helping them break through the confines of family experience and traditional customs in addition to providing psychological motivation to express their gender concepts, shape their self-image, construct gender power, and interpret intimate relationships, pushing them to become more reflective of the times, as well as more capable and authoritative.